Hydrogen at extreme pressures (Review Article) - Goncharov, Alexander F.; Howie, Ross T.; Gregoryanz, Eugene (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2013)
Here we review recent experimental and theoretical studies of hydrogen approaching metallization regime. Experimental techniques have made great advances over the last several years making it possible to reach previously unachievable conditions of pressure and temperature and to probe hydrogen at these conditions. Theoretical me-thods have also greatly improved; exemplified through the prediction of new structural and ordered quantum states. Recently, a new solid phase of hydrogen, phase IV, has been discovered in a high-pressure high-temperature domain. This phase is quite unusual structurally and chemically as it represents an intermediate state between common molecular and monatomic configurations. Moreover, it shows remarkable fluxional characteristics related to its quantum nature, which makes it unique among the solid phases, even of light elements. However, phase IV shows the presence of a band gap and exhibits distinct phonon and libron characteristic of classical solids. The quantum behavior of hydrogen in the limit of very high pressure remains an open question. Prospects of studying hydrogen at more extreme conditions by static and combined static-dynamic methods are also presented.